Understanding The Mathematical Consept Through The Development Of Student Worksheet (LKS) Model Of Discovery Guided For High School Students - Chanafi, Chanafi; Fatirul, Achmad Noor; Hartono, Hartono (International Journal for Educational and Vocational Studies, 2020)
The implementation of the 2013 curriculum in Indonesias education still faces many obstlacles. One of them is the lack of appropriate  teaching materials, it causes difficulties for both students and teachers during teaching and learning process. This development aims to produce a student worksheet with used guided discovery learning model for student grade X, analysing the appropriateness of the worksheet, and analysing students responses on the developed worksheet. The type of this study is Research and Development. Development model used in this study is the one according to Branch that is ADDIE which consists of analyse, design, development, implementation, and evaluation. The results showed a content worthiness score of 87.21% with very decent criteria, presentation worthiness of 89.09% with very decent criteria, linguistic worthiness of 83.64% with very decent criteria and graphics worthiness of 89.67% with very decent criteria. The average of the four components of the study and validation was 87.37% with very decent criteria. While the average score of the percentage of student responses was 83.13% with very good criteria. So it can be concluded that the Student Worksheet (LKS) developed was stated to be very suitable for use in the learning process and obtain positive responses from students